(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Respiratory syncytial virus (RSV) is a viral pathogen affecting the lungs mainly lower lobe causing infections. It is an enveloped RNA virus having a single stranded, negative sense genome. It belongs to the family Pneumoviridae and the genus Orthopneu Amovirus having two genomes A and B. RSV is one of the most important viral causes of bronchiolitis and pneumonia in infants and young children, and it also significantly affects elderly adults, patients that have gone under transplants and immuno-compromised patients. Worldwide RSV continues to be a major cause of hospital admissions. According to World Health Organization, an estimated value of 3.6 million hospitalizations and approximately 100 000 deaths each year among children younger than five years old are related to RSV. The RSV epidemic, unlike other respiratory viruses such as influenza happens each year, the RSV infections can always be seen in chilly weather such as late fall and winter. The Respiratory Syncytial Virus is highly contagious with an incubation period of 4 to 5 days and can spread through respiratory droplet or close contact with contaminated surface. Since RSV has heavy droplets, it cannot be aerosolized for long distances thus contact is the primary route of transmission.